Adaptive radar resource management - Moo, Peter W.; Ding, Zhen (Defence scientist) (Academic Press is an imprint of Elsevier, 2015)
Radar Resource Management (RRM) is vital for optimizing the performance of modern phased array radars, which are the primary sensor for aircraft, ships, and land platforms. Adaptive Radar Resource Management gives an introduction to radar resource management (RRM), presenting a clear overview of different approaches and techniques, making it very suitable for radar practitioners and researchers in industry and universities. Coverage includes: RRM's role in optimizing the performance of modern phased array radars The advantages of adaptivity in implementing RRMThe role that modelling and simulation plays in evaluating RRM performanceDescription of the simulation tool Adapt_MFRDetailed descriptions and performance results for specific adaptive RRM techniques.